Pengaruh Permainan Tradisional Dam-Daman Bangun Datar (Damtar) Terhadap Sikap Sosial Siswa Kelas Iv Sdn Cililitan - Hikmah Ramdani, Desta; Nugraha, M. Fahmi; Sunanih, Sunanih (Journal of Elementary Education: Strategies, Innovations, Curriculum, and Assesment, 2024)
This research aims to see the influence of Dam-daman Bangun Datar (DAMTAR) media on the social attitudes of class IV students at SDN Cililitan. This research uses a type of quantitative experimental research. This type of research uses a quasi experiment with a nonequivalent control group design. The population used was all class IV students at SDN Cililitan, totaling 26 students. The sample taken was using a random sampling technique. In this population design, it was divided into two control groups given conventional learning method (lecture) and the experimental group given learning treatment using Dam-daman Bangun Datar (DAMTAR) media. Data collection techniques were carried out by providing questionnaires (pretest and posttest), observation, interviews and documentation. The results of this research indicate that Dam-daman Bangun Datar (DAMTAR) media has an influence on the social attitudes of class IV students at SDN Cililitan. This is proven by the results of hypothesis testing using the independent sample t-test which was obtained with a sig (2-tailed) value of 0.001 < 0.05, so Ha was accepted and Ho was rejected. So it can be concluded that there is an influence of the use of Dam-daman Bangun Datar (DAMTAR) media on the social attitudes of class IV students at SDN Cililitan.